An Analysis of Herzberg’s Two-Factor Theory of Motivation and Employee Turnover in The BPO Industry - G. Reyes, Archie (International Journal of Management and Education in Human Development, 2024)
In today's competitive business environment, employees are the backbone of organizations, making their contributions invaluable. However, employee turnover remains a prevalent challenge across industries. This study examined the connection between motivation and employee turnover in the BPO industry, guided by Herzberg's Two-Factor Theory, wherein intrinsic and extrinsic factors were identified as the two motivational factors influencing an employee's motivation level. The research materials used were modified survey questionnaires by Tan and Waheed (2011): “Herzberg’s motivation-hygiene theory and job satisfaction in the Malaysian retail sector: the mediating effect of love of money.” Ayalew (2015), in his study, “The Impact of Job Satisfaction on Employee Turnover Intention. Furthermore, a descriptive research approach was used in this study. The general result for the intrinsic motivational factors, such as achievement, recognition, and growth, attained an overall mean of 4.02 and a standard deviation of 0.77 with a high descriptive equivalent. The extrinsic indicator yielded an overall mean of 3.72 and a standard deviation of 0.95, a satisfactory descriptive equivalent. Multiple Regression Analysis was used to establish a strong connection between intrinsic and extrinsic motivation and employee turnover. The analysis revealed a statistically significant relationship, with an R-square value of 0.429 and beta values of (-0.324, p<0.05) for intrinsic motivation and (Beta = -0.63, p<0.05) for extrinsic motivation, ultimately leading to the rejection of the hypothesis.